Association between Kaposi’s sarcoma-associated herpesvirus genotype and clinical types - Shohei Yogi; Haruna Ishikawa; Haruna Ishikawa; Aya Oshiro; Reo Yamazato; Chiharu Sakamoto; Yasuka Tanabe; Karina Uehara; Kiyoto Kurima; Shinichiro Kina; Kenzo Takahashi; Hirofumi Arakawa; et al. (Pathology and Oncology Research)
Kaposi’s sarcoma (KS) is a vascular intermediate malignant tumor classified into four clinical types: classic, AIDS-related, iatrogenic, and endemic. Kaposi’s sarcoma-associated herpesvirus (KSHV) is the causative agent of KS. Six KSHV genotypes (A, B, C, D, E, and F) classified by K1 or two genotypes (P and M) by K15 have been reported. However, whether the KSHV genotype affects clinical presentation remains elusive. Herein, we investigated the association between viral genotypes and clinical presentations in patients with KS in Okinawa, an endemic area in Japan. Classic KS caused by KSHV genotype C was identified as the most common clinical type of KS in Okinawa. Conversely, 80% of the patients with AIDS-related KS were associated with genotype A. According to K15 genotyping, the population of genotype M was higher than that of genotype P. Although genotype M accounted for most cases of both classic and iatrogenic KS in Okinawa, genotype P constituted the majority of AIDS-related KS. Regarding the association between the K1 and K15 genotypes, single genotype A was associated with genotype P, whereas single genotype C was associated with genotype M. These K1 and K15 associations in Okinawa differed from those in Europe and Africa. In terms of the association between viral genotype and clinical types, A/P tended to be associated with AIDS-related KS and genotype C/M tended to be associated with classic KS. The findings of the current study suggest that the KSHV genotype in Okinawa differs from that in other countries, which is related to the KSHV geographic distribution and population migration. Our data also suggest that the viral genotype in Okinawa is associated with clinical presentations.